The golden compass - Pullman, Philip (New York, Knopf, 1995)
Lyra Belaqua sets out to prevent her best friend and other kidnapped children from becoming subjects of gruesom experiments in the North.
5 and up
930
Keywords: Missing persons-experiments -- Fiction; Kidnapping -- Fiction; Fantasy; Arctic regions -- Fiction